PENGARUH FASILITAS TARIF DAN PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA FEYLOVE SALON DI BOYOLALI - Novi Putri Sukmawati; Nuning Lisdiana; Unna Ria Safitri (Journal of Social Sustainability Management, 2022)
This study aims to determine how much influence the facilities, tariffs and services partially have on the customer satisfaction of Feylove Salon in Boyolali. This study also aims to determine how much influence the provision of facilities, tariffs and services simultaneously on consumer satisfaction at Feylove Salon in Boyolali. The type of data in this study uses quantitative data. The data source uses primary and secondary data sources. Facilities, tariffs and services are independent variables and consumer satisfaction is the dependent variable. The population in this study are Feylove Salon consumers. Samples were taken as many as 100 respondents using the Simple Random Sampling technique. Based on statistical data analysis, the indicators in this study are valid and the variables are reliable. In the classical assumption test, the regression model is multicollinearity free, does not occur heteroscedasticity, and is normally distributed. And the results of this study indicate that the facilities, rates and services at Feylove Salon have a simultaneous effect on consumer satisfaction, this can be seen from the value of Fcount (25.916) > Ftable (2.699) with a significant level of 0.000. And this research has a partial effect on consumer satisfaction Feylove Salon this can be seen from the significant value of the facility 0.075> 0.05. Tariff has a positive and significant effect on consumer satisfaction Feylove Salon, this can be seen from the significant value of 0.000